1968
DOI: 10.1001/archpedi.1968.02100020046006
|View full text |Cite
|
Sign up to set email alerts
|

Cysts of the Oral Mucosa in Newborns

Abstract: CLINICALLY evident cysts of the alveolar and palatal mucosa are apparently a very common finding in newborns and infants and are often referred to as Epstein's pearls or Bohn's nodules. The cystic lesions have been described as white, raised, multiple nodules of maxillary and mandibular alveolar ridges and midpalatal region varying in size from a pin head to 2 or 3 mm. The majority of these cysts are inconspicuous and usually only the larger lesions are noticed. No treatment of these lesions is required as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

1974
1974
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 3 publications
3
23
0
Order By: Relevance
“…Friend et al [15] recorded alveolar cysts in 25% of children from Tennessee, USA. Cataldo and Berkman [16] reported a 36.5% prevalence of cysts on the maxillary alveolar ridge. Liu and Huang [12] reported cysts in 79% of Taiwanese newborns.…”
Section: Oral Anomaliesmentioning
confidence: 97%
“…Friend et al [15] recorded alveolar cysts in 25% of children from Tennessee, USA. Cataldo and Berkman [16] reported a 36.5% prevalence of cysts on the maxillary alveolar ridge. Liu and Huang [12] reported cysts in 79% of Taiwanese newborns.…”
Section: Oral Anomaliesmentioning
confidence: 97%
“…Regardless of their origin, nOCs tend to grow slowly in size, possibly in response to an increase in luminal hydrostatic pressure [5]. Some lesions may resolve spontaneously, such as palatal cysts of the newborn [6,7], whereas others such as thyroglossal duct cysts present a high recurrence rate if not treated aggressively [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some authors [24,25] found 80% and 94% prevalence of oral cysts in newborns, respectively.…”
Section: Discussionmentioning
confidence: 99%